Development of Innumerable, Expectedly Safe, and Aqueous Systems to Make Intramuscular Aqueous Injections (Solutions) of Poorly Water-soluble Drugs using Mixed Solvency Concept - Parihar, Ashwinee (Asian Journal of Pharmaceutics (AJP), 2022)
Background: The primary goal of this research is to investigate the concept of mixed solvency in terms of developing a large number of safe solvent systems for aqueous intramuscular injections that include water-soluble additives. As a result, pharmaceutical industries can use these solvent systems to provide intramuscular injections of drugs that are poorly water-soluble. Safe solubilizers’ solubilizing properties can be utilised to improve the solubility of poorly water-soluble drugs. Objective: The main purpose of this research is to provide pharmaceutical manufacturers with novel approaches for aqueous IM injections. Materials and Methods: In the present study, we employed sodium benzoate, sodium acetate, sodium citrate, valine, l-lysine, arginine, ethanol, Tween 80 and benzoic acid as solubilizers and ornidazole, paracetamol, aspirin, salicylic acid, gatifloxacin, naproxen, meloxicam, furosemide, piroxicam, acyclovir, fenofibrate, indomethacin, norfloxacin, and nimesulide. Furosemide was selected as the drug for the formulation of a typical aqueous IM injectable solution. For the drug identification, melting ranges were determined all the drugs using melting point apparatus (Analab Scientific). UV identification was also done for all drugs using UV-visible spectrophotometer (Shimadzu 1700). The pH of blend was estimated using pH meter (Cyber Scan). Drug and excipient interference studies were performed before formulation using UV-visible spectrophotometer. Drug and excipient interference studies also done before the formulation. The composition of formulation is L-lysine (3% w/v), sodium acetate (10% w/v), arginine (10% w/v), and Tween 80 (5% w/v). Results: By the solubility studies in different blends, the possibility of some IM injection solution can prepare such as furosemide (20 mg/2 ml), piroxicam (20 mg/2 ml), repaglinide (16 mg/3 ml), indomethacin (25 mg/ml), and acyclovir (20 mg/3 ml) can be produced. Furosemide: Chemical, physical, and freeze thaw studies were performed for the stability study of formulation. The formulation gives satisfactory results during physical and chemical stability studies. The pH of formulation was also performed and it was found similar to the pH of blend (pH-7). Conclusion: From this research work, it is clear that mixed solvency concept can be employed to develop a large numbers of expectedly safe aqueous IM injection solution type aqueous solvent systems for poorly water-soluble drugs. Thus, solubilizing power of safe additives can be employed to make marketable aqueous IM injections.